C40 granite high-performance mass concrete and preparation method thereof
By adding specific proportions of cement, fly ash and other materials to granite concrete, the poor adhesion of acid granite machine sand and gravel is solved, and the compressive strength, seepage resistance and crack resistance of concrete are improved, satisfying the The construction requirements of large-volume concrete extend the service life of the bridge.
Patent Information
- Application Number
- CN202411529020.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
In the existing granite concrete technology, the adhesion of acidic granite machine sand and gravel is poor, resulting in the concrete being prone to cracks, cracks and peeling, low compressive strength, poor permeability and crack resistance, and solidification of large-volume concrete. Fast speed and slow heat dissipation, making it difficult to meet construction requirements.
Using acid granite machined sand and gravel as the main materials, cement, fly ash, fume, limestone powder, gypsum, sodium tripolyphosphate, expansion agent, retarder and mixed water, and after thorough stirring and mixing, it is prepared. High-performance large-volume concrete of granite with high compressive strength, permeability, crack resistance and good volume stability.
It solves the problem of poor adhesion of acid granite machined sand and gravel, improves the compressive strength, seepage resistance and crack resistance of concrete, extends the solidification time, reduces the occurrence of temperature cracks, reduces the construction cost, and increases the The service life of the bridge.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, in particular to a C40 granite high-performance mass concrete and a preparation method thereof. Background Art
[0002] Among concrete materials, granite is an acidic rock with a pH value mostly between 6 and 7. Its main components are silicate minerals, especially silicon dioxide (SiO 2 ) content is more than 65%, making granite acidic. The existing granite concrete technology often has the following technical problems: (1) The machine-made sand and crushed stone made from granite have a pH value between 6 and 7, which makes it difficult to have affinity and adhesion with cement and other materials, which easily causes cracks, cracks and spalling in granite concrete, resulting in the early crack resistance of granite concrete being 456 to 532 mm. 2 / m 2 , electric flux is 1093~1235C, and carbonization depth is 11.6~14.1mm, which does not meet the requirements of L-Ⅳ, Q-Ⅳ, T-Ⅳ in the "Concrete Quality Control Standard" (GB 50164-2011) and electric flux ≤1000C in the "Technical Specification for Highway Bridge and Culvert Construction" (JTG / T3650-2020), reducing the durability of granite concrete and shortening the service life of bridges; (2) The machine-made sand and gravel made from granite have defects such as poor grading, more edges and flakes, and large crushing value due to the brittleness of granite. The mixed granite concrete mixture has a small or large amount of water precipitation, poor cohesion, and local segregation, resulting in the 28d compressive strength of granite concrete being 44.8MPa, which does not meet the "Ordinary Concrete Mix Design Code" (JGJ 55-2011) standard, the test strength is ≥48.2MPa; resulting in the granite concrete impermeability grade of P8, which does not meet the P10 impermeability grade requirement. Although granite has the advantages of hard and dense texture, high strength, weathering resistance, corrosion resistance, wear resistance, and low water absorption, it also has the above technical defects.
[0003] In a bridge project in the Guangdong Delta Plain, where alkaline limestone is scarce and acidic granite is abundant, the bridge 7# main pier cap is a dumbbell-shaped cap with a cap height of 5.0m. The plane outline of the entire cap and tie beam is 1075㎡, and the total concrete pouring volume is 6153.4m 3, the pedestal and tower base are made of C40 high-performance mass concrete. The existing mass concrete technology often has the following technical problems: Since cement hydration releases a large amount of heat, the mass concrete solidifies quickly, with an initial setting time of 683 to 876 minutes and a final setting time of 766 to 989 minutes, which does not meet the technical requirements of the initial setting time of 900 to 1200 minutes and the final setting time of ≥1200 minutes required for the construction of the mass concrete pedestal of this bridge; and because the heat dissipation of the mass concrete is slow and the temperature difference between the inside and outside is large, the mass concrete is prone to temperature cracks, and the early crack resistance of the concrete caused by the rapid evaporation of water on the surface of the mass concrete is 456 to 532 mm. 2 / m 2 , which does not meet the L-Ⅳ grade requirements of the "Concrete Quality Control Standard" (GB 50164-2011).
[0004] In the construction of bridge concrete, if qualified alkaline limestone gravel and river sand are purchased from a long distance, the construction cost will be increased beyond the project budget. In order to ensure the quality of bridge construction and the project cost does not exceed the project budget, it is necessary to use local materials and process acidic granite into machine-made sand and gravel as the main concrete materials for the construction of this bridge.
[0005] Therefore, given the acidic and brittle properties of granite, and the fact that large-volume concrete is prone to temperature cracks and shrinkage cracks, how to prepare high-performance large-volume granite concrete with high compressive strength, good impermeability, crack resistance and volume stability is an urgent problem that needs to be solved in the construction of this bridge. Summary of the invention
[0006] The invention provides a C40 granite high-performance mass concrete and a preparation method thereof, so as to solve the technical problems that the machine-made sand and crushed stone of acidic granite have poor adhesion, the granite concrete mixture has poor workability, poor encapsulation, sand and gravel separation, and the granite concrete has low compressive strength, poor crack resistance, poor permeability and poor volume stability.
[0007] According to one aspect of the present invention, a C40 granite high-performance mass concrete is provided, comprising the following raw materials: cement, fly ash, silica fume, limestone powder, gypsum, machine-made sand, crushed stone, sodium tripolyphosphate, expansion agent, retarder, mixing water,
[0008] The mass ratio of cement, fly ash, silica fume, limestone powder, gypsum, machine-made sand, crushed stone, sodium tripolyphosphate, expansion agent, retarder and mixing water is 296.00-302.00: 39.62-40.42: 39.62-40.42: 19.81-20.21: 1.19-1.21: 719.00-747.00: 1035.00-1077.00: 0.119-0.121: 31.70-32.34: 7.92-8.08: 159.00-161.00;
[0009] The machine-made sand and crushed stone are processed from acidic granite.
[0010] Furthermore, the mass ratio of the cement, fly ash, silica fume, limestone powder, gypsum, machine-made sand, crushed stone, sodium tripolyphosphate, expansion agent, retarder and mixing water is 299.00:40.02:40.02:20.01:1.20:733:1056:0.12:32.02:8.00:160.00.
[0011] Furthermore, the silica fume is SF90 grade powdered silica fume with a particle size of 0.1 to 0.3 μm.
[0012] Furthermore, the limestone powder is a fine powder produced in the process of producing crushed stone and machine-made sand, and the residue on a 45 μm square hole sieve is no more than 12.3%.
[0013] Furthermore, the machine-made sand is made from acidic granite through crushing, has a fineness modulus of 2.80-2.90, is medium sand, has a mud content of 0%, and a single-stage maximum crushing value of no more than 16.0%.
[0014] Furthermore, the crushed stone is made by crushing acidic granite, and has a nominal particle size of 5 to 25 mm and is a continuous particle size crushed stone.
[0015] Furthermore, the expansion agent is a calcium sulphoaluminate concrete expansion agent.
[0016] Furthermore, the retarder is a polycarboxylic acid-based HPWR-R type high performance water reducing agent.
[0017] Furthermore, the sodium tripolyphosphate adopts white crystalline powder of type I (high temperature type) sodium tripolyphosphate.
[0018] According to another aspect of the present invention, there is also provided a method for preparing C40 granite high-performance mass concrete, the preparation method comprising the following steps:
[0019] Firstly, machine-made sand, fly ash, silica fume, limestone powder and gypsum are sequentially added into a mixer and dry-mixed to prepare a first mixture;
[0020] adding cement to the first mixture and mixing to prepare a second mixture;
[0021] Add crushed stone and part of mixing water to the second mixture in sequence and mix to prepare the third mixture;
[0022] Adding a retarder and an expansion agent to the third mixture in sequence and stirring to prepare a fourth mixture;
[0023] Sodium tripolyphosphate and the balance mixing water are added to the fourth mixture in sequence and stirred to prepare a C40 granite high-performance mass concrete mixture.
[0024] The present invention has the following beneficial effects:
[0025] (1) The present invention uses acidic granite machine-made sand and gravel as the main materials of concrete, and by adding a certain proportion of cement, fly ash, silica fume, limestone powder, gypsum, sodium tripolyphosphate, expansion agent, retarder and mixing water raw materials, fully stirring and mixing, a granite high-performance large-volume concrete with high compressive strength, good impermeability, crack resistance and volume stability is prepared. The present invention not only solves the problems of using local materials, saving resources, reducing pollution and waste, and reducing engineering construction costs, so that the cost of bridge engineering does not exceed the engineering budget and is in a controllable state; at the same time, it also solves the technical problems of poor adhesion of acidic granite machine-made sand and gravel, poor workability of granite concrete mixture, poor encapsulation, sand and gravel separation, and low compressive strength, crack resistance, impermeability and volume stability of granite concrete, and has the beneficial effects of simple construction process operation, low construction cost and green environmental protection.
[0026] (2) On the premise of ensuring that the compressive strength and workability (slump) of granite concrete meet the technical requirements, the amount of cement saved is 18 to 24 kg / m 3 , reducing the hydration heat of cement (under laboratory conditions, P.O42.5 ordinary Portland cement: 3d is 4320~5760kJ, 7d is about 4860~6480kJ), thereby reducing the internal temperature of granite concrete. It not only prevents the granite concrete from generating temperature cracks due to temperature stress exceeding its own resistance, but also saves cement consumption and reduces the construction cost of bridge caps.
[0027] (3) The slump of concrete is reduced by 5 to 10 mm, the expansion of concrete is increased by 20 to 50 mm, the cohesiveness, water retention and segregation of concrete are improved, and granite concrete with good fluidity and uniform distribution can be obtained, which makes it easier for granite concrete to flow and lay, reduces the workload of vibrating granite concrete, facilitates construction operations, and improves construction efficiency; makes granite concrete more evenly distributed, reduces gaps and defects, thereby improving the integrity and durability of the pedestal; according to the shape, size and reinforcement conditions of the pedestal, by increasing the expansion of granite concrete, specific construction requirements can be better met to ensure the quality of engineering construction.
[0028] (4) The air content of concrete is increased by 0.5-1.0%. Due to the rolling and floating effects of bubbles, the workability and stability of machine-made sand and crushed stone concrete made from granite are improved; the lubricity of concrete is increased, the friction resistance of pipelines is reduced, thereby improving the pumpability of concrete; the surface area and viscosity of concrete are increased, thereby reducing concrete bleeding and sedimentation; and the impermeability of concrete is improved.
[0029] (5) The initial setting time of concrete is extended to 304-369 minutes and the final setting time is extended to 356-455 minutes, thereby slowing down the solidification speed of granite concrete, thereby prolonging the heat dissipation process of granite concrete, reducing shrinkage cracks caused by evaporation of water in granite concrete, helping to maintain the working performance and slump of granite concrete, making granite concrete easier to operate and shape during construction, and better controlling the early and late strength of granite concrete, thereby improving the overall quality and durability of granite concrete.
[0030] (6) Reduced the early cracking resistance of concrete by 70 to 142 mm 2 / m 2 , thereby reducing the early cracks of granite concrete, effectively inhibiting the occurrence of cracks and plastic shrinkage deformation of granite concrete, and increasing the elastic modulus of granite concrete, thereby improving the crack resistance and volume stability of granite concrete.
[0031] (7) It reduces the electric flux of concrete by 55 to 250°C, reduces the penetration of moisture and other harmful substances into granite concrete, enhances the anti-penetration ability of granite concrete, and thus improves the density and stability of granite concrete.
[0032] (8) The carbonization depth of concrete is reduced by 1.6 to 4.9 mm, which effectively protects the internal steel bars of the pedestal from corrosion, thereby improving the durability and safety of the pedestal; the original strength and hardness of the granite concrete are maintained, thereby improving the durability of the pedestal and extending its service life.
[0033] (9) The concrete impermeability is improved by two grades, which reduces the chemical corrosion and physical damage of water and other liquids to the cap, protects the reinforcing materials such as steel bars inside the cap concrete from corrosion, and enhances the durability of the cap; reduces the internal damage of granite concrete caused by water penetration, extends the service life of the cap, and reduces the cost of repair or reconstruction; enhances the impermeability of granite concrete, prevents water intrusion, avoids the volume change and deformation of the cap caused by water, and improves the safety of the cap concrete.
[0034] (10) The 7-day compressive strength of concrete is increased by 1.4-4.0 MPa, the 28-day compressive strength is increased by 1.0-3.8 MPa, and the 60-day compressive strength is increased by 1.7-3.8 MPa, thereby improving the bearing capacity, durability, safety and stability of the pedestal structure, reducing the project maintenance cost, reducing the project construction cost, and increasing the service life of the bridge.
[0035] In addition to the above-described objects, features and advantages, the present invention has other objects, features and advantages. The present invention will be described in further detail below. DETAILED DESCRIPTION
[0036] The following is a detailed description of the embodiments of the present invention, but the present invention can be implemented in many different ways as defined and covered below.
[0037] The embodiment of the first aspect of the present invention provides a C40 granite high-performance mass concrete, comprising the following raw materials: cement, fly ash, silica fume, limestone powder, gypsum, machine-made sand, crushed stone, sodium tripolyphosphate, expansion agent, retarder, mixing water,
[0038] The mass ratio of cement, fly ash, silica fume, limestone powder, gypsum, machine-made sand, crushed stone, sodium tripolyphosphate, expansion agent, retarder and mixing water is 296.00-302.00: 39.62-40.42: 39.62-40.42: 19.81-20.21: 1.19-1.21: 719.00-747.00: 1035.00-1077.00: 0.119-0.121: 31.70-32.34: 7.92-8.08: 159.00-161.00;
[0039] The machine-made sand and crushed stone are processed from acidic granite.
[0040] This application is based on the construction of C40 high-performance large-volume concrete for the 7# main pier cap of an A-shaped single-tower cable-stayed bridge in the Guangdong Delta Plain area. The 7# main pier cap of the bridge is a dumbbell-shaped cap with a cap height of 5.0m. The plane outline of the entire cap and tie beam is 1075㎡, and the total concrete pouring volume is 6153.4m 3The abutment and tower base are made of C40 high-performance mass concrete. Since this bridge is located in an area with a shortage of alkaline limestone and abundant acidic granite, if qualified alkaline limestone gravel and river sand are purchased from a long distance during bridge construction, the construction cost will be increased beyond the project budget. In order to ensure the quality of bridge construction and the project cost does not exceed the project budget, local materials must be used to process acidic granite into machine-made sand and gravel as the main concrete materials for the construction of this bridge.
[0041] (1) The acidic properties of granite lead to the problem of poor adhesion of acidic granite machine-made sand and gravel. This application adds gypsum, limestone powder, sodium tripolyphosphate, and fly ash raw materials to granite concrete, which solves the problem of poor adhesion of acidic granite machine-made sand and gravel, and realizes the use of acidic granite machine-made sand and gravel as the main concrete materials for the construction of this bridge. Local materials are used to save resources, reduce pollution and waste, reduce construction costs, and meet the strategic requirements of energy conservation, environmental protection, and sustainable development. The above-mentioned gypsum, limestone powder, sodium tripolyphosphate, and fly ash raw materials have the following specific roles:
[0042] This application is in granite concrete:
[0043] 1) Adding gypsum (CaSO 4 ·2H 2 O), increase Ca in granite concrete 2+ ions, Ca 2+ Ions and CO in granite concrete 3 2- The ions combine to form CaCO 3 .
[0044] 2) Add limestone powder, because its fine particles can fill the gaps between cement particles and the pores of granite concrete, improve the particle grading of the cementitious material system, lubricate the granite machine-made sand and gravel, and enhance the bonding between granite machine-made sand and gravel.
[0045] 3) Add gypsum and limestone powder to act on the acidic granite machine-made sand and gravel together, and form a layer of calcium carbonate with long-term stable performance on the surface of its particles, just like the acidic granite machine-made sand and gravel are wrapped by a layer of calcium carbonate and transformed into alkaline machine-made sand and gravel. They have good affinity and adhesion with cement and other substances, and change the properties of the acidic granite machine-made sand and gravel from the physical properties, so that the acidic granite machine-made sand and gravel meet the characteristics of aggregates for high-performance large-volume concrete, thereby meeting the various performance requirements of high-performance large-volume concrete.
[0046] 4) Sodium tripolyphosphate is added because of its weak alkalinity, which fills the pores and cracks in the granite concrete and reacts with the calcium hydroxide in the granite concrete to form stable compounds, preventing the alkali-aggregate reaction of the granite concrete, avoiding the expansion and destruction of the granite concrete due to chemical reactions, and preventing the cracking and spalling of the granite concrete, thereby improving the durability and thermal stability of the granite concrete.
[0047] 5) Add fly ash, the active ingredient Si in fly ash 2 and A1 2 0 3 It reacts chemically with cement hydration products in the presence of mixing water or free water formed by the addition of silica fume and limestone powder to generate substances such as hydrated calcium silicate and hydrated calcium aluminate, which fill the pores of cement hydration products, reduce the porosity inside the granite concrete, refine the pore size, change the pore structure, and improve the bonding effect of the various components of the granite concrete.
[0048] (2) The brittle nature of granite causes problems such as poor workability, easy water seepage, poor encapsulation, and sand-gravel separation in granite concrete mixtures, resulting in low compressive strength and poor impermeability of granite concrete. The present application adds fly ash, silica fume, limestone powder, sodium tripolyphosphate, expansion agent, and retarder raw materials to granite concrete, thereby solving the problems of poor workability, easy water seepage, poor encapsulation, and sand-gravel separation in granite concrete mixtures, and significantly improving the compressive strength and impermeability of granite concrete. The above fly ash, silica fume, limestone powder, sodium tripolyphosphate, expansion agent, and retarder raw materials play the following specific roles:
[0049] This application is in granite concrete:
[0050] 1) Adding fly ash: ① It acts as a "ball bearing" in the granite concrete mixture, reducing the water demand of cement slurry, improving the workability of fresh granite concrete, filling the pores in cement slurry, and improving the density of hardened granite concrete; ② It can make up for the lack of fine powder in granite concrete, block the water seepage channel, and help reduce the water seepage rate; ③ Increase the powder in the cement slurry, increase the volume of the cement slurry, improve the cohesion of granite concrete, and inhibit the segregation and water seepage of granite concrete; ④ Due to the bearing ball effect of fly ash, the fluidity of granite concrete is improved and the loss of fluidity over time is reduced; ⑤ Improve the interface structure of granite concrete, turn coarse particles into fine particles, and turn coarse pores into fine pores, thereby improving the density of granite concrete, and the strength and impermeability of granite concrete are improved.
[0051] 2) Adding silica fume: ① It plays a ball-rolling role between cement particles that are similar to plates and blocks and have more large particles, fills the gaps between cement, reduces the water used in cement gaps to form more free water, and is mixed with cement, fly ash, limestone powder, gypsum, sodium tripolyphosphate, expansion agent, and retarder raw materials to form a large-flowing cement slurry, which wraps and fills the gaps between the dense granite machine-made sand and crushed stone skeletons, avoids sand and gravel separation, reduces the porosity of granite concrete, and improves the pore structure of granite concrete, thereby improving the wrapping, density, strength and impermeability of granite concrete; ② Increase the total surface area of granite concrete aggregates, increase the air content in granite concrete, and the tiny bubbles play a ball-rolling role in granite concrete, so that the slump of granite concrete is improved. The increased bubbles increase the cohesion of granite concrete, and the bubbles bond to the solid particles, reducing the solid particles. ③Increase the fine powder in the cement slurry to increase the volume of the cement slurry, improve the cohesiveness and water retention of the granite concrete, inhibit the segregation and bleeding of the granite concrete, and improve the durability of the granite concrete; ④The active components of silica fume react with the calcium hydroxide produced in the cement hydration process to generate more hydrated calcium silicate gel (CSH), which increases the strength of the granite concrete and improves the durability of the granite concrete; ⑤When the ratio of silica fume to cement increases, the active components in the silica fume participate more in the hydration reaction of the cement, resulting in a decrease in the Ca / Si ratio in the hydration product, so that the CSH gel can combine with more other ions, such as aluminum ions and alkali metal ions, to enhance the structural stability of the CSH gel and further improve the strength and durability of the granite concrete.
[0052] 3) Adding limestone powder: ① Because its particles are nearly spherical and there are more fine particles, it plays a ball-rolling role between cement particles that are nearly plate-shaped, block-shaped and have more large particles, optimizes the gradation of cement particles, fills the gaps between cement, reduces the water used in cement gaps to form more free water, and is mixed with mixed fine materials composed of cement, fly ash, silica fume, gypsum, sodium tripolyphosphate, expansion agent, and retarder raw materials to form a high-flow cement slurry, which wraps and fills the gaps between the dense granite machine-made sand and crushed stone skeletons, avoids sand and gravel separation, reduces the porosity of granite concrete, and improves the pore structure of granite concrete, thereby improving the encapsulation and formation of granite concrete. ① Increase the total surface area of granite concrete aggregates and the air content in granite concrete. Tiny bubbles play a ball-like role in granite concrete, which improves the slump of granite concrete. The increased bubbles increase the cohesion of granite concrete. The bubbles adhere to solid particles, reduce the sinking of solid particles and water flow, block the water seepage channel of granite concrete, and reduce the water seepage of granite concrete. ③ Increase the fine powder in cement slurry to increase the volume of cement slurry, improve the cohesion and water retention of granite concrete, inhibit the segregation and water seepage of granite concrete, and improve the durability of granite concrete.
[0053] 4) Adding sodium tripolyphosphate: ① Promote the hydration of cement, so that the crystal morphology of the hydration product grows regular and is more evenly distributed, which is beneficial to the strength growth of granite concrete and improves the compressive strength of granite concrete; ② Fill the micropores and capillaries inside the granite concrete, reduce the porosity of the granite concrete, improve the durability of the granite concrete, and overcome the disadvantage of adding expansion agent to produce bubbles and increase the porosity of the granite concrete; ③ Reduce the water-cement ratio of granite concrete and increase the density and durability of granite concrete; ④ Sodium tripolyphosphate can reduce the adhesion and internal friction angle of granite concrete, improve the workability of granite concrete, improve the fluidity and plasticity of granite concrete, make granite concrete easier to construct and vibrate, and improve construction efficiency; ⑤ In the preparation and use of granite concrete, adding an appropriate amount of sodium tripolyphosphate can form a thin film on the surface of granite concrete, reduce the occurrence of oxidative corrosion, thereby avoiding aging and damage of granite concrete, reducing the permeability of granite concrete, and making it have better anti-seepage performance.
[0054] 5) Adding expansion agent: ① Generate bubbles in granite concrete to form a fine pore structure, reduce the capillary pores inside granite concrete, reduce the water permeability, increase the density and hardness of granite concrete, and improve the impermeability, durability and seismic resistance of granite concrete; ② In granite concrete, generate expansive crystalline substances through chemical reactions, so that granite concrete can expand moderately, thereby establishing pre-compression stress under steel bars and other constraints, offsetting the tensile stress caused by the shrinkage of granite concrete, reducing the formation of cracks, effectively compensating for shrinkage, making the performance of granite concrete more stable, and improving the crack resistance and durability of granite concrete; ③ Control the hydration reaction process of granite concrete, delay the setting time of granite concrete, make granite concrete have sufficient fluidity during the construction process, and maintain plasticity for a certain period of time, adjust the fluidity and setting time of concrete, and improve the construction performance of concrete; ④ Adjust the chemical reaction process of granite concrete, promote better solidification and gelation of cement particles, and improve the early and late strength and hardness of granite concrete; ⑤ Fill the micro cracks in granite concrete, increase the cohesion of granite concrete, and improve the compressive strength of granite concrete.
[0055] 6) Adding retarders can produce tiny bubbles in granite concrete. The bubbles have the same charge as cement particles, and electrostatic repulsion will occur between the two, causing the cement particles to disperse. The bubbles can physically isolate the cement particles and prevent them from agglomerating. At the same time, the bubbles themselves can play a role similar to that of ball bearings, promoting the sliding of cement particles and improving the fluidity of granite concrete.
[0056] (3) The large-volume concrete has the problems of fast solidification speed, slow heat dissipation, large temperature difference between inside and outside, and rapid evaporation of water, which lead to the easy occurrence of temperature cracks and shrinkage cracks in the large-volume concrete. The present application adds limestone powder, gypsum, retarder, sodium tripolyphosphate, expansion agent, and fly ash raw materials to the granite concrete, which solves the problems of fast solidification speed, slow heat dissipation, large temperature difference between inside and outside, and rapid evaporation of water in the large-volume concrete, effectively controls the temperature cracks and shrinkage cracks in the large-volume granite concrete, and improves the crack resistance, impermeability and volume stability of the granite concrete. The above-mentioned limestone powder, gypsum, retarder, sodium tripolyphosphate, expansion agent, and fly ash raw materials play the following specific roles:
[0057] This application is in granite concrete:
[0058] 1) Adding limestone powder can replace part of cement, reduce cement consumption, reduce hydration heat, reduce cracks in granite concrete caused by temperature rise, improve the working performance of granite concrete, and improve the durability of granite concrete.
[0059] 2) Add gypsum to the cement tricalcium aluminate (C3 A) reacts with calcium hydroxide to form calcium sulphoaluminate hydrate which is insoluble in water. 3 A) The particle surface forms a coating layer, which prevents tricalcium aluminate (C 3 A) further hydration reduces the solubility of aluminate in the solution, so that the hydration product of calcium aluminate cannot be separated, increasing the slow-reacting tricalcium silicate (C 3 S) colloidal solution concentration, thereby delaying the cement setting time, and then extending the initial and final setting time of granite concrete, preventing the granite concrete from hardening prematurely, allowing the expansive agent to have more sufficient time to play an expansion role in the hydration process, more effectively compensating for the shrinkage of granite concrete, making the granite concrete produce moderate expansion to establish prestress, offsetting the tensile stress generated in the hardening process of granite concrete, reducing the formation of cracks, and thus improving the strength, crack resistance and durability of granite concrete.
[0060] 3) Adding retarder, because its molecular structure contains hydroxyl (-OH), carboxyl (-COOH), sulfonic acid (-SO 3 H), polyethoxy (-OCH 2 CH 2 ) and other functional groups. On the one hand, the main chain is adsorbed on the surface of cement particles to prevent the particles from contacting with water. The high grafting density of carboxyl (-COOH) and sulfonic acid (-SO 3 H) provides electrostatic repulsion and combines with calcium to form a calcium-rich protective layer. A small amount of hydroxyl (-OH) complexes with exposed hydrated silica ions, effectively reducing the concentration of calcium and silicon ions in the solution and preventing the release of ions. On the other hand, polyethoxy (-OCH 2 CH 2 ) long side chain and a small amount of hydroxyl (-OH) form hydrogen bonds with water, produce water film three-dimensional protection and steric hindrance effect, increase the thickness of the hydration layer, delay cement hydration, and effectively inhibit the initial tricalcium aluminate (C 3 A) and tricalcium silicate (C 3 S) hydration, slowing down the solidification speed of granite concrete, thereby prolonging the heat dissipation process of granite concrete, reducing the evaporation of water in granite concrete, and overcoming the disadvantage of plastic cracking of granite concrete after adding silica fume.
[0061] 4) Adding sodium tripolyphosphate: ① With Ca in cement 2+The ion reaction generates calcium phosphate salts that are insoluble in water, which cover the surface of cement particles to form a chemical adsorption layer, hindering the hydration reaction of cement particles and slowing down the hydration rate, thereby playing a retarding role, delaying the setting time of cement and inhibiting the slump loss of granite concrete over time, ensuring operability during construction, reducing liquid phase ion concentration and supersaturation, changing the morphology of dihydrate gypsum crystals, further affecting the hydration process of cement, reducing the volume shrinkage of hydration products, reducing shrinkage deformation and cracking of granite concrete, and improving the durability of granite concrete; ② Slowing down the release of hydration heat and hardening speed, prolonging the heat dissipation process of granite concrete, reducing the evaporation of water on the surface of granite concrete, overcoming the disadvantages of shrinkage cracks caused by the evaporation of water on the surface of granite concrete after the addition of silica fume, thereby improving the construction performance and durability of granite concrete.
[0062] 5) Adding expansion agent: ① After dissolving in water, a large amount of gas is generated, forming tiny bubbles that are dispersed in the granite concrete, which expands the volume of the granite concrete, reduces the shrinkage of the granite concrete, and increases the volume stability of the granite concrete, thereby reducing the internal stress of the granite concrete and improving the concrete's impermeability and durability; ② Adding expansion agent to granite concrete can compensate for the shrinkage of granite concrete in equal amounts, and has the function of filling and blocking capillary pores, greatly improving the granite concrete's anti-seepage and anti-cracking capabilities; ③ Adding expansion agent to granite concrete can produce a certain amount of expansion to compensate for the shrinkage of granite concrete, reduce the hydration heat effect inside the granite concrete, reduce the generation of temperature gradients, reduce the effective stress level of granite concrete, and then reduce the internal temperature of the granite concrete and increase the diffusion of heat in the granite concrete.
[0063] 6) Adding fly ash can improve the interface structure of granite concrete, turn coarse particles into fine particles, and coarse pores into fine pores, reduce the temperature rise of granite concrete, and delay the time when the maximum temperature peak occurs. It is extremely beneficial to the crack resistance and anti-seepage of high-performance large-volume granite concrete, reduce hydration heat, reduce temperature difference shrinkage, and reduce costs.
[0064] The present invention prepares the various components of the mixing station on site according to the types and specifications of the components of the granite high-performance mass concrete, and stacks them in compartments according to the types and specifications, and marks and manages them against rainwater. The relevant quality indicators of the components of the granite high-performance mass concrete are inspected before entering the site, and all inspection results must meet the requirements of the relevant national and industry construction technical specifications, product standards or technical documents before they can be used.
[0065] The cement used is China Resources P.O42.5 ordinary Portland cement. The test results show that the density is 3.04g / cm 3 , with a specific surface area of 348m 2 / kg, initial setting time is 244min, final setting time is 316min, stability is qualified, 28d compressive strength is 52.6MPa, 28d flexural strength is 7.4MPa, all test indicators meet the technical requirements of P.O42.5 in the "General Portland Cement" (GB 175) standard. The 3d hydration heat of China Resources P.O42.5 ordinary Portland cement is 240kJ / kg, and the 7d hydration heat is 270kJ / kg.
[0066] The fly ash used is the Class F Grade I fly ash from Datang Power Plant with stable quality and uniform material, and its dosage is 10% of the total cementitious material mass. The test results show that the density is 2.57g / cm 3 The fineness is 8.6%, the water requirement ratio is 90%, the moisture content is 0.1%, the loss on ignition is 4.3%, and the strength activity index is 84%. Its quality meets the technical requirements for Class I fly ash in the standard "Fly ash used in cement and concrete" (GB / T 1596).
[0067] Silica fume, also known as microsilica powder, is produced by collecting and treating the smoke and dust that escapes with the exhaust gas during the high-temperature smelting of industrial silicon and ferrosilicon in industrial electric furnaces through special capture devices. 2 The content accounts for about 90% of the total smoke, and the particle size is very small, and the average particle size is almost nanometer level, so it is called silica fume. Since silica fume has a finer fineness than cement particles, most of the particles are less than 1μm, and the average particle size is 0.1-0.3μm, which is one hundredth of the size of cement particles. This application uses SF90 grade powdered silica fume, and its dosage is 10% of the total cementitious material mass. The test results are: the density is 2.36g / cm 3 , with a specific surface area of 21.2m 2 / g, water requirement ratio is 112%, moisture content is 0.3%, SiO 2 The content is 92.46%, the loss on ignition is 1.3%, and the activity index is 115%. Its quality meets the technical requirements of SF90 grade silica fume in the standard "Silica Fume for Mortar and Concrete" (GB / T 27690).
[0068] Limestone powder is fine powder produced in the process of producing crushed stone and machine-made sand, and its dosage is 5% of the total cementitious material mass. The test results show that the density is 2.68g / cm 3 , MB value is 0.32g / kg, 45μm square hole sieve residue is 12.3%, calcium carbonate content is 90.68%, moisture content is 0.4%, compressive strength ratio (28d) is 81%, and its quality meets the technical requirements of LIA grade limestone powder in "Limestone Powder for Cement, Mortar and Concrete" (GB / T35164) standard.
[0069] Gypsum, also known as calcium sulfate, is a soft sulfate mineral composed of calcium sulfate dihydrate with a chemical formula of CaSO 4 ·2H 2 O, pH 7. Gypsum (CaSO 4 ·2H 2 O) is made from natural gypsum ore after calcination and crushing. The density of Shandong gypsum is 2.35g / cm 3 White powder gypsum, the addition amount of which is 0.3% of the total cementitious material mass.
[0070] The machine-made sand is made of hard, dense and high-strength acidic granite after multiple crushing processes. The test results show that the fineness modulus is 2.83, which is medium sand, and the apparent density is 2540kg / m 3 , Bulk density is 1640kg / m 3 , mud content is 0%, methylene blue MB value test is qualified, mud block content is 0.3%, single-stage maximum crushing value is 16.0%, and all test indicators are in line with the technical requirements for Class II machine-made sand in Zone 2 of the "Construction Sand" (GB / T 14684) standard.
[0071] The crushed stone is made of hard, dense and high-strength acidic granite, which is crushed and processed multiple times to produce a nominal particle size of 5-25mm continuous particle size. The test results show that the particle size is well-graded, the mud content is 0.3%, the mud block content is 0%, the needle-like particle content is 6.6%, the crushing value is 8.0%, and the apparent density is 2580kg / m 3 , bulk density is 1560kg / m 3 The saturated compressive strength of the rock is 92.2MPa, and all test indicators meet the technical requirements for Class II crushed stone in the standard "Pebble and Crushed Stone for Construction" (GB / T 14685).
[0072] Sodium tripolyphosphate is an amorphous water-soluble linear polyphosphate inorganic compound with the chemical formula Na 5 P 3 O 10 , density is 2.52g / cm 3 , white crystalline powder, easily soluble in water. This application uses type I (high temperature type) sodium tripolyphosphate, which has high thermal stability and hygroscopicity, and its dosage is 0.03% of the total gelling material mass.
[0073] The expansion agent is calcium sulfoaluminate concrete expansion agent, which is generated by the reaction of calcium oxide, aluminum oxide and calcium sulfate at 1000-1250℃. 4 Al 6 SO 16 , also written as 3(CA)·CaSO 4 or C 4 A6 S, which reacts with water to form hydrated calcium sulfoaluminate. This application uses a powdered high-efficiency CSA concrete expansion agent. The test results show that the density is 3.26g / cm 3 , specific surface area is 253m 2 / kg, and its 7d limited expansion rate in water is 0.0375%. Its quality meets the technical requirements of Type I expansive agent in the standard "Concrete Expansive Agent" (GB / T23439), and its dosage is 8% of the total cementitious material mass.
[0074] The retarder adopts HPWR-R type high performance water reducing agent (slow setting type) of polycarboxylic acid series, water agent, water reduction rate is 26%, and its dosage is 2.0% of the total cementitious material mass. Its quality meets the technical requirements of high performance slow setting water reducing agent in the "Concrete Admixture" (GB8076) standard.
[0075] The mixing water used is drinking water. Upon inspection, its quality meets the requirements for water used in concrete in the Standard for Water Used in Concrete (JGJ63).
[0076] Furthermore, the mass ratio of the cement, fly ash, silica fume, limestone powder, gypsum, machine-made sand, crushed stone, sodium tripolyphosphate, expansion agent, retarder and mixing water is 299.00:40.02:40.02:20.01:1.20:733:1056:0.12:32.02:8.00:160.00.
[0077] Furthermore, the sodium tripolyphosphate adopts white crystalline powder of type I (high temperature type) sodium tripolyphosphate.
[0078] According to an embodiment of the second aspect of the present invention, there is also provided a method for preparing C40 granite high-performance mass concrete, the preparation method comprising the following steps:
[0079] Firstly, machine-made sand, fly ash, silica fume, limestone powder and gypsum are sequentially added into a mixer and dry-mixed to prepare a first mixture;
[0080] adding cement to the first mixture and mixing to prepare a second mixture;
[0081] Add crushed stone and part of mixing water to the second mixture in sequence and mix to prepare the third mixture;
[0082] Adding a retarder and an expansion agent to the third mixture in sequence and stirring to prepare a fourth mixture;
[0083] Sodium tripolyphosphate and the balance mixing water are added to the fourth mixture in sequence and stirred to prepare a C40 granite high-performance mass concrete mixture.
[0084] The following examples describe the present disclosure in more detail, and these examples are intended for illustrative purposes only.
[0085] Example 1
[0086] The present embodiment provides a C40 granite high-performance mass concrete, comprising the following raw materials: cement: fly ash: silica fume: limestone powder: gypsum: machine-made sand: crushed stone: sodium tripolyphosphate: expansion agent: retarder: mixing water in a mass ratio of 301.00: 40.30: 40.30: 20.15: 1.21: 721: 1066: 0.121: 32.24: 8.06: 159 (unit: kg / m 3 )(water-cement ratio is 0.39, sand ratio is 40%).
[0087] Example 2
[0088] The present embodiment provides a C40 granite high-performance mass concrete, comprising the following raw materials: cement: fly ash: silica fume: limestone powder: gypsum: machine-made sand: crushed stone: sodium tripolyphosphate: expansion agent: retarder: mixing water in a mass ratio of 299.00: 40.02: 40.02: 20.01: 1.20: 733: 1056: 0.120: 32.02: 8.00: 160.00 (unit: kg / m 3 )(water-cement ratio is 0.40, sand ratio is 41%).
[0089] Example 3
[0090] The present embodiment provides a C40 granite high-performance mass concrete, comprising the following raw materials: cement: fly ash: silica fume: limestone powder: gypsum: machine-made sand: crushed stone: sodium tripolyphosphate: expansion agent: retarder: mixing water in a mass ratio of 296.00: 39.63: 39.63: 19.81: 1.19: 746: 1046: 0.119: 31.70: 7.93: 161 (unit: kg / m 3 )(water-cement ratio is 0.41, sand ratio is 42%).
[0091] Comparative Example 1
[0092] This comparative example is basically the same as Example 1, except that limestone powder, gypsum, sodium tripolyphosphate and expansion agent are not added, and the mass ratio of cement: fly ash: silica fume: machine-made sand: crushed stone: retarder: mixing water is 325:41:41:732:1084:8.14:159 (unit: kg / m 3 )(water-cement ratio is 0.39 and sand ratio is 40%).
[0093] Comparative Example 2
[0094] This comparative example is basically the same as Example 2, except that limestone powder, gypsum, sodium tripolyphosphate and expansion agent are not added, and the mass ratio of cement: fly ash: silica fume: machine-made sand: crushed stone: retarder: mixing water is 320:40:40:747:1075:8.00:160 (unit: kg / m 3 )(water-cement ratio is 0.40 and sand ratio is 41%).
[0095] Comparative Example 3
[0096] This comparative example is basically the same as Example 3, except that limestone powder, gypsum, sodium tripolyphosphate and expansion agent are not added, and the mass ratio of cement: fly ash: silica fume: machine-made sand: crushed stone: retarder: mixing water is 314:39:39:768:1061:7.84:161 (unit: kg / m 3 )(water-cement ratio is 0.41 and sand ratio is 42%).
[0097] Preparation of C40 granite high performance mass concrete in Examples 1-3:
[0098] In the concrete component design room with an indoor temperature of 5℃~30℃, 500L (0.50m 3 ) For concrete mixture, use a 150kg electronic scale with a sensitivity of 1g to weigh the following materials:
[0099] Example 1: Weigh the following items respectively: 150.500 kg (dry mass) of cement, 20.150 kg (dry mass) of fly ash, 20.150 kg (dry mass) of silica fume, 10.075 kg (dry mass) of limestone powder, 0.605 kg (dry mass) of gypsum, 360.500 kg (dry mass) of machine-made sand, 533.000 kg (dry mass) of crushed stone, 0.060 kg (dry mass) of sodium tripolyphosphate, 16.120 kg (dry mass) of expansion agent, 4.030 kg (aqueous solution) of retarder, and 79.500 kg of mixing water to prepare a concrete mixture.
[0100] Example 2: Weigh the following qualities respectively: 149.500 kg (dry mass) of cement, 20.010 kg (dry mass) of fly ash, 20.010 kg (dry mass) of silica fume, 10.005 kg (dry mass) of limestone powder, 0.600 kg (dry mass) of gypsum, 366.500 kg (dry mass) of machine-made sand, 528.000 kg (dry mass) of crushed stone, 0.060 kg (dry mass) of sodium tripolyphosphate, 16.010 kg (dry mass) of expansion agent, 4.000 kg (aqueous solution) of retarder, and 80.000 kg of mixing water to prepare a concrete mixture.
[0101] Example 3: Weigh the following masses respectively: 148.000 kg (dry mass) of cement, 19.815 kg (dry mass) of fly ash, 19.815 kg (dry mass) of silica fume, 9.905 kg (dry mass) of limestone powder, 0.595 kg (dry mass) of gypsum, 373.000 kg (dry mass) of machine-made sand, 523.000 kg (dry mass) of crushed stone, 0.060 kg (dry mass) of sodium tripolyphosphate, 15.850 kg (dry mass) of expansion agent, 3.965 kg (aqueous solution) of retarder, and 80.500 kg of mixing water to prepare a concrete mixture.
[0102] Preparation method of concrete: firstly, add weighed mass of machine-made sand, fly ash, silica fume, limestone powder and gypsum into an indoor concrete mixer in turn and dry mix for 60 seconds to prepare a first mixture; secondly, add weighed mass of cement into the first mixture and stir for 30 seconds to prepare a second mixture; again, add weighed mass of crushed stone and part of mixing water into the second mixture in turn and stir for 60 seconds to prepare a third mixture; then, add weighed mass of retarder and expansion agent into the third mixture in turn and stir for 30 seconds to prepare a fourth mixture; finally, add weighed mass of sodium tripolyphosphate and the balance of mixing water into the fourth mixture in turn and stir for 120 seconds to prepare a C40 granite high-performance large-volume concrete mixture.
[0103] Preparation of concrete in Comparative Examples 1-3:
[0104] Comparative Example 1: Weigh the following masses respectively: 162.500 kg (dry mass) of cement, 20.500 kg (dry mass) of fly ash, 20.500 kg (dry mass) of silica fume, 366.000 kg (dry mass) of machine-made sand, 542.000 kg (dry mass) of crushed stone, 4.070 kg (aqueous solution) of retarder and 79.500 kg of mixing water, and mix them into a concrete mixture.
[0105] Comparative Example 2: Weigh the following masses respectively: 160.000 kg (dry mass) of cement, 20.000 kg (dry mass) of fly ash, 20.000 kg (dry mass) of silica fume, 373.500 kg (dry mass) of machine-made sand, 537.50 kg (dry mass) of crushed stone, 4.000 kg (aqueous solution) of retarder and 80.000 kg of mixing water, and mix them to prepare a concrete mixture.
[0106] Comparative Example 3: Weigh the following masses respectively: 157.000 kg (dry mass) of cement, 19.500 kg (dry mass) of fly ash, 19.500 kg (dry mass) of silica fume), 384.000 kg (dry mass) of machine-made sand, 530.500 kg (dry mass) of crushed stone, 3.920 kg (aqueous solution) of retarder and 80.500 kg of mixing water, and mix the concrete mixture.
[0107] Preparation method of concrete: first, add weighed mass of machine-made sand, fly ash and silica fume into an indoor concrete mixer in turn, dry mix for 60 seconds to prepare a first mixture; secondly, add weighed mass of cement into the first mixture and stir for 30 seconds to prepare a second mixture; again, add weighed mass of crushed stone and part of mixing water into the second mixture in turn, stir for 60 seconds to prepare a third mixture; finally, add weighed mass of retarder and the remaining mixing water into the third mixture in turn, stir for 120 seconds to prepare a granite concrete mixture.
[0108] Experimental Case
[0109] The concrete mixtures of Examples 1 to 3 were tested for performance indicators of apparent density, slump, change in slump over time after 1 h, expansion, cohesion, water retention, air content, setting time, segregation, early crack resistance of concrete, electric flux of concrete, carbonation depth of concrete, impermeability of concrete, and compressive strength of concrete according to the determination methods in the standards "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" (GB / T 50080), "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081), and "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082). The test results are shown in Table 1.
[0110] Table 1-1 Performance index test results of Examples 1 to 3
[0111]
[0112] Table 1-2 Performance index test results of Examples 1 to 3
[0113]
[0114]
[0115] It can be seen from Table 1-1 and Table 1-2 that the various performance indicators of the granite concrete prepared in the above Examples 1 to 3 all comply with the "Ordinary Concrete Mix Design Code" (JGJ 55-2011), "Technical Code for Highway Bridge and Culvert Construction" (JTG / T3650-2020), "Concrete Quality Control Standard" (GB 50164-2011), "Massive Concrete Construction Standard" (GB50496-2018), "High Performance Concrete Evaluation Standard" (JGJ / T 385-2015) and other technical requirements specified in the standards and design requirements, as well as meet the technical requirements required for the construction of mass concrete for the bridge cap.
[0116] The concrete mixtures of Comparative Examples 1 to 3 were tested for performance indicators of apparent density, slump, change in slump over 1h, expansion, cohesion, water retention, air content, setting time, segregation, early crack resistance of concrete, electric flux of concrete, carbonation depth of concrete, impermeability of concrete, and compressive strength of concrete according to the test methods in the standard "Standard for Performance Test Methods of Ordinary Concrete Mixtures" (GB / T 50080), "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081), and "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082). The test results are shown in Table 2.
[0117] Table 2-1 Performance index test results of comparative examples 1 to 3
[0118]
[0119] Table 2-2 Performance index test results of comparative examples 1 to 3
[0120]
[0121]
[0122] It can be seen from Table 2-1 and Table 2-2 that the granite concrete prepared in Comparative Examples 1 to 3 without adding limestone powder, gypsum, sodium tripolyphosphate, and expansion agent raw materials has the following technical problems:
[0123] The concrete mixtures of Comparative Examples 2 to 3 have a small amount or a large amount of water separated out; the concrete mixture of Comparative Example 3 has poor cohesion and local segregation; the initial setting time of the concrete of Comparative Examples 1 to 3 is 683 to 876 minutes, and the final setting time is 766 to 989 minutes; the early crack resistance of the concrete of Comparative Examples 2 to 3 is 456 to 532 mm 2 / m 2 , the concrete electrical flux is 1093~1235C, the concrete carbonization depth is 11.6~14.1mm, and the concrete impermeability grade is P8; the 28d compressive strength of the concrete in Comparative Example 3 is 44.8MPa.
[0124] The above-mentioned technical problems do not comply with the technical requirements specified in the "Code for Design of Ordinary Concrete Mix" (JGJ 55-2011), "Technical Specifications for Highway Bridge and Culvert Construction" (JTG / T3650-2020), "Concrete Quality Control Standard" (GB 50164-2011), "Massive Concrete Construction Standard" (GB 50496-2018), and "High Performance Concrete Evaluation Standard" (JGJ / T 385-2015), as well as the design requirements, and do not meet the technical requirements required for the construction of massive concrete for the bridge pedestal.
[0125] The concrete data in the above-mentioned Examples 1-3 and Comparative Examples 1-3 are all experimental data in the laboratory. In order to further verify the effect of the present invention, the concrete insulation temperature rise calculation of the outdoor example and the mixing verification of the outdoor mixing station are carried out using the same raw materials and proportions as the concrete in Example 2.
[0126] 1. Calculation of concrete insulation temperature rise for outdoor examples
[0127] (1) Known conditions. In the outdoor example, the amount of cementitious material W per cubic meter of concrete is 400.25 kg / m 3 ; The specific heat capacity C of concrete is 0.92 kJ / (kg·℃); The mass density ρ of concrete is measured to be 2390 kg / m 3 ; According to the 3d hydration heat of China Resources P.O42.5 ordinary Portland cement of 240kJ / kg and 7d hydration heat of 270kJ / kg, the fly ash and silica fume content is 10% of the total cementitious material mass, the cement is ordinary Portland cement with λ of 0.88, the concrete construction mold entry temperature is calculated as 30℃, and the total hydration heat Q of the cementitious material is calculated according to the standard calculation method of clauses B.1.1, B.1.2 and B.1.3 in Appendix B.1 of the "Standard for Construction of Mass Concrete" (GB 50496-2018) in the adiabatic temperature rise of concrete, which is 286.57kJ / kg; the concrete age t is 60d; the corresponding coefficient m of the single cubic cementitious material is calculated to be 1.604.
[0128] (2) Calculation method. The outdoor example is calculated according to the standard calculation method of clauses B.1.1, B.1.2, B.1.3, B.1.4 and B.1.5 in Appendix B.1 Adiabatic temperature rise of concrete of the "Standard for Construction of Mass Concrete" (GB 50496-2018), and the adiabatic temperature rise value T(t) of concrete at 60 days of age is calculated as follows:
[0129]
[0130] Where: T(t)- adiabatic temperature rise value when concrete age is t (℃);
[0131] W- cementitious material consumption per cubic meter of concrete (kg / m 3 );
[0132] C-specific heat capacity of concrete [kJ / (kg·℃)];
[0133] ρ-mass density of concrete (kg / m 3 );
[0134] Q-total heat of hydration of cementitious materials (kJ / kg);
[0135] t-concrete age (d);
[0136] m-corresponding coefficient of unilateral cementitious material related to cement type, dosage and mold entry temperature, etc.
[0137] (3) Calculation results. According to calculation, the adiabatic temperature rise of the concrete in the outdoor example at 60 days of age is 43.83°C, which meets the requirements of the "Ordinary Concrete Mix Design Code" (JGJ55-2011) and the "Massive Concrete Construction Standard" (GB 50496-2018) that the adiabatic temperature rise of concrete should not exceed 50°C.
[0138] 2. Carry out C40 granite high performance large volume concrete mixing plant mixing verification at an outdoor mixing plant, including the following technical contents:
[0139] (1) When purchasing mixing equipment, select and customize the concrete mixing output per hour to be no less than 75m 3 The JS750 type concrete forced mixer has an automatic metering standard with 2 batching bins.
[0140] (2) After the mixing equipment is debugged, the measuring instruments of the mixing equipment must be regularly calibrated by a statutory metrology inspection agency for static calibration and the weighing accuracy of each silo must be dynamically calibrated during the use of the mixing equipment. The allowable deviation of the weighing accuracy must comply with the provisions of relevant national and industry construction technical specifications.
[0141] (3) Check the temperature of the mixing plant and each component material. According to actual measurements: the temperature in the mixing plant is 30°C; the temperature of cement and silica fume is 45°C, the temperature of fly ash is 40°C, the temperature of machine-made sand, crushed stone, limestone powder, gypsum, sodium tripolyphosphate, expansion agent and retarder is 30°C, the temperature of mixing water is 10°C; the time required for concrete to leave the station and reach the construction site is 1 hour.
[0142] (4) Check the moisture content of machine-made sand and gravel in the on-site material preparation warehouse of the mixing station.
[0143] (5) Calculate the material supply required for each mixing bin for each batch of concrete.
[0144] The mixing quantity per plate shall not exceed 75% of the rated discharge capacity of the mixer (i.e. 500L or 0.50m 3 ) calculation, stirring 1m 3 Concrete. According to the measured moisture content of machine-made sand and crushed stone, calculate the mixing amount of cement, fly ash, silica fume, limestone powder, gypsum, machine-made sand, crushed stone, sodium tripolyphosphate, expansion agent, retarder and mixing water for each batch.
[0145] The amount of mixing water is: the calculated amount of mixing water minus the water content in the machine-made sand and gravel.
[0146] (6) Permissible deviation of the metering of each component material for each mixing pan (by mass): According to Article 6.15.10 of the Technical Specifications for Highway Bridge and Culvert Construction (JTG / T3650-2020), the permissible deviation of the metering of machine-made sand and crushed stone is ±2%, and the permissible deviation of the metering of cement, fly ash, silica fume, limestone powder, gypsum, sodium tripolyphosphate, expansion agent, retarder and mixing water is ±1%. The concrete mixture of the outdoor embodiment is obtained.
[0147] (7) Check the uniformity and color consistency of concrete mixture.
[0148] (8) Check the temperature of concrete mixture leaving the machine.
[0149] 3. For the concrete mixture of the outdoor embodiment, the performance index tests of apparent density, slump, slump change over time for 1h, expansion, cohesion, water retention, air content, setting time, segregation, early crack resistance of concrete, concrete electric flux, concrete carbonization depth, concrete impermeability, and concrete compressive strength were carried out according to the determination methods in the standards of "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" (GB / T50080), "Standard for Test Methods of Physical and Mechanical Properties of Concrete" (GB / T 50081), and "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" (GB / T 50082); the adiabatic temperature rise value of the concrete at the age of 60d was calculated according to the standard calculation method of adiabatic temperature rise of concrete in Appendix B.1 of the "Standard for Construction of Mass Concrete" (GB 50496-2018), and the test results are shown in Table 3.
[0150] Table 3-1 Performance index test results of Examples 1 to 3, outdoor examples, and Comparative Examples 1 to 3
[0151]
[0152] Table 3-2 Performance index test results of Examples 1 to 3, outdoor examples, and Comparative Examples 1 to 3
[0153]
[0154]
[0155] The test results in Table 3-1 and Table 3-2 show that: when comparing the test results of Example 2 with those of the outdoor example, the parallel differences in the performance index tests of apparent density, slump, change in slump over 1h, expansion, cohesion, water retention, air content, setting time, segregation, early crack resistance of concrete, concrete electrical flux, concrete carbonization depth, concrete impermeability, and concrete compressive strength of the two all meet the requirements of relevant standards and specifications.
[0156] The raw material of the granite concrete prepared in the embodiment of the present invention contains limestone powder, gypsum, sodium tripolyphosphate, and an expansion agent, and a synergistic effect is produced between the components:
[0157] ① Add limestone powder. The fine particles of limestone powder can be filled into the gaps between cement particles and the pores of granite concrete, improve the particle gradation of the cementitious material system, enhance the density and strength of granite concrete, and reduce the drying shrinkage of granite concrete. Limestone powder has low adsorption of water, which is manifested as a small water demand ratio or water reduction effect, which helps to improve the fluidity of granite concrete. As an inert material, limestone powder can promote the hydration process of cement, reduce the hydration heat of granite concrete, reduce the water bleeding rate of granite concrete, and reduce the slump loss. a. Used in combination with gypsum, it can jointly improve the water retention and cohesion of granite concrete, increase the fluidity and plasticity of granite concrete, and make it easier to operate during mixing, transportation and pouring. The reinforcing effect of gypsum combined with the filling effect of limestone powder can significantly improve the physical properties and durability of granite concrete. b. When used in combination with sodium tripolyphosphate, under the effect of sodium tripolyphosphate preventing the alkali-aggregate reaction of granite concrete, limestone powder can more effectively play the role of improving the physical properties of granite concrete (reducing water bleeding rate and reducing slump loss). c. When used in combination with an expansive agent, the shrinkage compensation effect of the expansive agent and the filling effect of limestone powder complement each other, thereby improving the crack resistance of granite concrete; limestone powder can improve the physical properties of granite concrete, help the expansive agent to be more evenly distributed in the granite concrete to produce expansion stress, compensate for the shrinkage of granite concrete, and thus prevent the occurrence of cracks in granite concrete; it not only enhances the crack resistance and durability of granite concrete, improves the early and late strength of granite concrete, but also reduces the drying shrinkage and permeability problems of granite concrete, thereby improving the overall quality and service life of granite concrete.
[0158] ② Add gypsum to react with calcium hydroxide in granite concrete to form ettringite crystal particles, so that granite concrete can expand moderately to establish prestress, offset the tensile stress generated in the hardening process of granite concrete, reduce the formation of cracks, and thus improve the strength, crack resistance and durability of granite concrete. It reacts with calcium aluminate in granite concrete to form stable compounds, delaying the initial and final setting time of granite concrete, preventing granite concrete from hardening prematurely, giving the expansive agent more time to expand during the hydration process, and more effectively compensating for the shrinkage of granite concrete. It can reduce the surface cracking problem of granite concrete caused by too fast evaporation of water, thereby improving the impermeability and durability of granite concrete, maintaining good performance in long-term use, controlling the expansion of granite concrete to a certain extent, and ensuring the stability of granite concrete. a. Used in combination with limestone powder, it can jointly improve the water retention and cohesion of granite concrete, increase the fluidity and plasticity of granite concrete, and make it easier to operate during mixing, transportation and pouring; the filling effect of limestone powder combined with the strengthening effect of gypsum can significantly improve the physical properties and durability of granite concrete. b. When used in combination with sodium tripolyphosphate, since the hydration reaction of gypsum is an exothermic reaction, its reaction speed is very fast. If the reaction speed cannot be controlled, the gypsum will harden prematurely, thus affecting the quality and performance of granite concrete. After mixing with sodium tripolyphosphate, sodium tripolyphosphate can promote the slow hydration reaction of gypsum, thereby controlling the hardening speed of gypsum and improving the strength and durability of gypsum. Sodium tripolyphosphate can also improve the crystal morphology and microstructure of gypsum, making it more dense and uniform, and improve the crystallinity and hydration degree of gypsum, thereby improving the density and durability of granite concrete. c. When used in combination with an expansion agent, the expansion agent can produce moderate expansion in the granite concrete to establish pre-compression stress, offset the tensile stress generated by the shrinkage of the granite concrete, reduce the formation of cracks, effectively compensate for shrinkage, and make the performance of granite concrete more stable. The combination of the two can significantly improve the crack resistance and durability of granite concrete.
[0159] ③ Adding sodium tripolyphosphate forms a chemical adsorption layer on the surface of cement particles, which hinders the hydration of cement particles, thereby playing a retarding role, delaying the setting time of cement and inhibiting the slump loss of granite concrete over time, ensuring operability during construction. Although sodium tripolyphosphate, as a concrete retarder, reduces the early strength of granite concrete, it does not affect the 28-day compressive strength of granite concrete. Sodium tripolyphosphate can also improve the impermeability of granite concrete, reduce water penetration, thereby improving the durability of granite concrete, and enhance the crack resistance of granite concrete, reducing cracks caused by shrinkage. Sodium tripolyphosphate is weakly alkaline and reacts with calcium hydroxide in granite concrete to form stable compounds, preventing alkali-aggregate reaction of granite concrete and avoiding expansion and destruction of granite concrete due to chemical reactions. Sodium tripolyphosphate can also improve the workability of granite concrete, making granite concrete easier to construct and vibrate, and improving construction efficiency. a. When used in combination with limestone powder, limestone powder can improve the physical properties and durability of concrete, while sodium tripolyphosphate can prevent alkali-aggregate reaction of granite concrete and improve the workability of granite concrete. The combination of the two can give full play to their respective advantages and comprehensively improve the physical, mechanical properties and durability of granite concrete. b. When used in combination with gypsum, sodium tripolyphosphate can promote the slow hydration reaction of gypsum, thereby controlling the hardening speed of gypsum and improving the strength and durability of gypsum. Sodium tripolyphosphate can also improve the crystal morphology and microstructure of gypsum, making it more dense and uniform, and improve the crystallinity and hydration degree of gypsum, thereby improving the density and durability of granite concrete. c. When used in combination with an expansion agent, it complements the expansion effect of the expansion agent to overcome the technical problem that sodium tripolyphosphate delays the setting time of cement, resulting in low early strength of granite concrete, and jointly improve the long-term performance and seismic resistance of granite concrete.
[0160] ④ Adding expansion agent, in granite concrete, through chemical reaction, expandable crystalline substances are generated, so that granite concrete can expand moderately, thereby establishing pre-compression stress under steel and other constraints, offsetting the tensile stress caused by the shrinkage of granite concrete, reducing the formation of cracks, effectively compensating for shrinkage, making the performance of granite concrete more stable, and improving the crack resistance and durability of granite concrete. The expansion agent produces bubbles in granite concrete, forming a fine pore structure, reducing the capillary pores inside the granite concrete, reducing the permeability of water, and improving the anti-permeability of granite concrete. The expansion agent can also improve the pore structure of granite concrete, increase the density and hardness of granite concrete, thereby improving the durability and seismic resistance of granite concrete. The expansion agent can also improve the early and late strength of granite concrete, especially in humid environments. a. Used in combination with limestone powder, the physical properties of granite concrete are improved by limestone powder, making it easier for the expansion agent to be evenly distributed in the granite concrete, giving play to the expansion stress of the expansion agent, compensating for shrinkage, and preventing cracks. b. When used in combination with gypsum, gypsum can delay the initial and final setting time of granite concrete, prevent premature hardening, and make it easier for the expansive agent to have more time to expand during the hydration process of granite concrete, and more effectively compensate for the shrinkage of granite concrete. c. When used in combination with sodium tripolyphosphate, it can complement the expansion effect of the expansive agent to overcome the technical problem that sodium tripolyphosphate delays the setting time of cement, resulting in low early strength of granite concrete, and jointly improve the long-term performance and seismic resistance of granite concrete.
[0161] In summary, through the interaction between the components of limestone powder, gypsum, sodium tripolyphosphate, and expansion agent raw materials and reasonable component design, it is ensured that each component plays its best effect in granite concrete, which not only meets the compressive strength requirements of granite concrete, but also significantly improves the working performance, crack resistance, impermeability and volume stability of granite concrete, ensuring that granite concrete can maintain good structure and function in various environments.
[0162] The invention adopts acidic granite machine-made sand and crushed stone as main concrete materials, adds a certain proportion of cement, fly ash, silica fume, limestone powder, gypsum, sodium tripolyphosphate, expansion agent, retarder and mixing water raw materials, fully stirs and mixes, and prepares a technical means of high-performance large-volume granite concrete with high compressive strength, good impermeability, crack resistance and volume stability. It not only solves the problem of using local materials, saving resources, reducing pollution and waste, and reducing construction costs, so that the cost of bridge projects does not exceed the project budget and is in a controllable state; at the same time, it also solves the technical problems of poor adhesion of acidic granite machine-made sand and crushed stone, poor workability of granite concrete mixture, poor encapsulation, sand and gravel separation, and low compressive strength, crack resistance, impermeability and volume stability of granite concrete. It can achieve: ① Reduce the cement hydration heat and the internal temperature of granite concrete; ② Improve the fluidity and distribution uniformity of granite concrete, reduce the vibration workload of granite concrete, facilitate construction operations, and improve construction efficiency; ③ Improve the workability and stability of machine-made sand and crushed stone concrete processed from granite; ④ Delay the setting of granite concrete The solidification speed is improved, the heat dissipation process of granite concrete is prolonged, and shrinkage cracks caused by evaporation of water in granite concrete are reduced; ⑤ The early cracks in granite concrete are reduced, and the crack resistance and volume stability of granite concrete are improved; ⑥ The anti-permeability of granite concrete is enhanced, and the density and stability of granite concrete are improved; ⑦ The steel bars inside the pedestal are protected from rust, and the durability and safety of the pedestal are improved; ⑧ The anti-permeability of granite concrete is enhanced, water intrusion is prevented, the volume change and deformation of the pedestal caused by water are avoided, and the safety of the pedestal concrete is improved; ⑨ The bearing capacity, durability, safety and stability of the pedestal structure are improved, the project maintenance cost is reduced, the project construction cost is reduced, and the service life of the bridge is improved.
[0163] In addition to the above technical effects, the invention also has the following technical effects:
[0164] (1) On the premise of ensuring that the compressive strength and workability (slump) of granite concrete meet the technical requirements, the amount of cement saved is 18-24 kg / m 3 , reducing the hydration heat of cement (under laboratory conditions, P.O42.5 ordinary Portland cement: 3d is 4320~5760kJ, 7d is about 4860~6480kJ), thereby reducing the internal temperature of granite concrete. It not only prevents the granite concrete from generating temperature cracks due to temperature stress exceeding its own resistance, but also saves cement consumption and reduces the construction cost of bridge caps.
[0165] (2) The slump of concrete is reduced by 5 to 10 mm, the expansion of concrete is increased by 20 to 50 mm, the cohesiveness, water retention and segregation of concrete are improved, and granite concrete with good fluidity and uniform distribution can be obtained, which makes it easier for granite concrete to flow and lay, reduces the workload of vibrating granite concrete, facilitates construction operations, and improves construction efficiency; makes granite concrete more evenly distributed, reduces gaps and defects, thereby improving the integrity and durability of the pedestal; according to the shape, size and reinforcement conditions of the pedestal, by increasing the expansion of granite concrete, specific construction requirements can be better met to ensure the quality of engineering construction.
[0166] (3) The air content of concrete is increased by 0.5-1.0%. Due to the rolling and floating effects of bubbles, the workability and stability of machine-made sand and crushed stone concrete made from granite are improved; the lubricity of concrete is increased, the friction resistance of pipelines is reduced, thereby improving the pumpability of concrete; the surface area and viscosity of concrete are increased, thereby reducing concrete bleeding and sedimentation; and the impermeability of concrete is improved.
[0167] (4) The initial setting time of concrete is extended to 304-369 minutes and the final setting time is extended to 356-455 minutes, thereby slowing down the solidification speed of granite concrete, thereby prolonging the heat dissipation process of granite concrete, reducing shrinkage cracks caused by evaporation of water in granite concrete, helping to maintain the working performance and slump of granite concrete, making granite concrete easier to operate and shape during construction, and better controlling the early and late strength of granite concrete, thereby improving the overall quality and durability of granite concrete.
[0168] (5) Reduced the early cracking resistance of concrete by 70 to 142 mm 2 / m 2 , thereby reducing the early cracks of granite concrete, effectively inhibiting the occurrence of cracks and plastic shrinkage deformation of granite concrete, and increasing the elastic modulus of granite concrete, thereby improving the crack resistance and volume stability of granite concrete.
[0169] (6) It reduces the electric flux of concrete by 55 to 250°C, reduces the penetration of moisture and other harmful substances into granite concrete, enhances the anti-penetration ability of granite concrete, and thus improves the density and stability of granite concrete.
[0170] (7) The carbonization depth of concrete is reduced by 1.6 to 4.9 mm, which effectively protects the internal steel bars of the foundation from corrosion, thereby improving the durability and safety of the foundation; the original strength and hardness of the granite concrete are maintained, thereby improving the durability of the foundation and extending its service life.
[0171] (8) The concrete impermeability was improved by two grades, which reduced the chemical corrosion and physical damage to the cap by water and other liquids, protected the reinforcing materials such as steel bars inside the cap concrete from corrosion, and enhanced the durability of the cap; reduced the internal damage of the granite concrete caused by water penetration, extended the service life of the cap, and reduced the cost of repair or reconstruction; enhanced the impermeability of the granite concrete, prevented water intrusion, avoided the volume change and deformation of the cap caused by water, and improved the safety of the cap concrete.
[0172] (9) The 7-day compressive strength of concrete is increased by 1.4 to 4.0 MPa, the 28-day compressive strength is increased by 1.0 to 3.8 MPa, and the 60-day compressive strength is increased by 1.7 to 3.8 MPa, thereby improving the bearing capacity, durability, safety and stability of the pier structure, reducing the project maintenance cost, reducing the project construction cost, and increasing the service life of the bridge.
[0173] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A C40 granite high performance mass concrete, characterized in that: The raw materials include the following components: cement, fly ash, silica fume, limestone powder, gypsum, machine-made sand, crushed stone, sodium tripolyphosphate, expansion agent, retarder, mixing water, The mass ratio of cement, fly ash, silica fume, limestone powder, gypsum, machine-made sand, crushed stone, sodium tripolyphosphate, expansion agent, retarder and mixing water is 296.00-302.00: 39.62-40.42: 39.62-40.42: 19.81-20.21: 1.19-1.21: 719.00-747.00: 1035.00-1077.00: 0.119-0.121: 31.70-32.34: 7.92-8.08: 159.00-161.00; The machine-made sand and crushed stone are processed from acidic granite.
2. The C40 granite high performance mass concrete according to claim 1, characterized in that: The mass ratio of the cement, fly ash, silica fume, limestone powder, gypsum, machine-made sand, crushed stone, sodium tripolyphosphate, expansion agent, retarder and mixing water is 299.00:40.02:40.02:20.01:1.20:733:1056:0.12:32.02:8.00:160.
00.
3. The C40 granite high performance mass concrete according to claim 1, characterized in that: The silica fume is SF90 grade powdered silica fume with a particle size of 0.1 to 0.3 μm.
4. The C40 granite high performance mass concrete according to claim 1, characterized in that: The limestone powder is a fine powder produced in the process of producing crushed stone and machine-made sand, and the residue on a 45 μm square hole sieve is no more than 12.3%.
5. The C40 granite high performance mass concrete according to claim 1, characterized in that: The machine-made sand is made by crushing acidic granite, has a fineness modulus of 2.80-2.90, is medium sand, has a mud content of 0%, and a single-stage maximum crushing value of no more than 16.0%.
6. The C40 granite high performance mass concrete according to claim 1, characterized in that: The crushed stone is made by crushing acidic granite, and has a nominal particle size of 5 to 25 mm and continuous particle size.
7. The C40 granite high performance mass concrete according to claim 1, characterized in that: The expansive agent is a calcium sulphoaluminate concrete expansive agent.
8. The C40 granite high performance mass concrete according to claim 1, characterized in that: The retarder is a polycarboxylic acid-based HPWR-R type high performance water reducing agent.
9. The C40 granite high performance mass concrete according to claim 1, characterized in that: The sodium tripolyphosphate adopts the white crystalline powder of type I sodium tripolyphosphate.
10. A method for preparing C40 granite high-performance mass concrete, characterized in that: Using the raw material of C40 granite high-performance mass concrete according to any one of claims 1 to 9, the preparation method comprises the following steps: Firstly, machine-made sand, fly ash, silica fume, limestone powder and gypsum are sequentially added into a mixer and dry-mixed to prepare a first mixture; adding cement to the first mixture and mixing to prepare a second mixture; Add crushed stone and part of mixing water to the second mixture in sequence and mix to prepare the third mixture; Adding a retarder and an expansion agent to the third mixture in sequence and stirring to prepare a fourth mixture; Sodium tripolyphosphate and the balance mixing water are added to the fourth mixture in sequence and stirred to prepare a C40 granite high-performance mass concrete mixture.